Penguatan Nilai Damai Sejahtera dalam Perspektif Lukas 2:14 di GBT Yahweh Jireh Bontang - Fianus Tandiongan; Tri Astuti; Joko Priyono (Devotion: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to implement a Christmas sermon ministry to strengthen the understanding and internalization of the value of peace among the congregation of GBT Yahweh Jireh Bontang. The activity was conducted on December 8, 2025, using a participatory-transformative approach through a structured Christmas worship service. This activity was attended by 120 congregations, including pastors in the city of Bontang. The methods included contextual sermon delivery, congregational reflection, and participatory observation. The results indicate an increased understanding of peace not only as a spiritual concept but also as a value influencing social relationships. This activity also encouraged the internalization of peace in daily life. Therefore, the Christmas sermon ministry proves to be an effective medium for strengthening spiritual and social values within the congregation.